ARTIFICIAL INTELLIGENCE-BASED JAPANESE LANGUAGE TEACHING: OPPORTUNITIES AND LIMITATIONS - Mulekova Linara Ramilevna (Web of Journals Publishing, 2026)
This article explores the possibilities and limitations of teaching Japanese using AI. It analyzes AI technologies, language learning applications, and interactive tools. At the same time, issues such as translation errors, contextual understanding limitations, and the necessity of real communication are discussed. In conclusion, while AI is an effective aid in language learning, it should be used with caution.
Keywords: Artificial Intelligence, Japanese language, language teaching, interactive learning, machine translation.